Similar Energy Expenditure During BodyPump and Heavy Load Resistance Exercise in Overweight Women - Rustaden, Anne Mette; Gjestvang, Christina; Bø, Kari; Haakstad, Lene Annette Hagen; Paulsen, Gøran (Frontiers in Physiology, 2020)
Purpose: High-repetition, low-load resistance exercise in group class settings has gained popularity in recent years, with BodyPump as a prime example. For individuals using exercise for body-weight management, the energy expenditure during exercise is of interest. Therefore, we herein aimed to estimate the energy expenditure during a session of BodyPump and a time-matched session of heavy load resistance training in overweight women (BMI ≥ 25.0). Method: Eighteen women participated in the study (mean age 35.4 years ±10.2, BMI 30.4 kg/m2 ±4.8), ten exercising BodyPump (50-100 repetitions each muscle group) and eight performed a heavy load session (8 repetition maximum x 3 sets). The energy expenditure was assessed with indirect calorimetry during the sessions and for two intervals at rest during the recovery phase: 0-20 and 120-140 min after the sessions. Results: The BodyPump group lifted significantly more loads than the heavy load group (19485 kg ±2258 vs 15616 kg ±2976, p=0.006), while energy expenditure was similar with 302 kcal ±67 and 289 kcal ±69 in BodyPump and heavy load group, respectively (p=0.69). With no group differences, the resting metabolic rate was elevated with 15-22% two hours after exercise. Conclusion: Overweight women achieved an energy expenditure of approximately 300 kcal (4.7 kcal per min) during a single session of BodyPump, which was similar with the women performing a single session of heavy load resistance exercise.